Reviews Film. Issue 1 (1st March 2016) - Bennett, John; Archer, Sam; Nalbantoglu, Karsu; Bye, Joseph
The Lobster (2015) Ireland/UK/Greece/France/Netherlands/USA Director Yorgos Lanthimos Runtime 118 minutesAmerican Psycho (2000) USA Director Mary Harron Runtime 98 minutesWhiplash (2014) United States Director Damian Chazelle Runtime 106 minsThe Babadook (2014) Australia Director Jennifer Kent Runtime 93 minutes